2021
DOI: 10.18009/jcer.1017362
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Online EFL Instructors’ Teaching Satisfaction during Pandemic

Abstract: In 2020, institutions had to shift to online education because of the health issues raised globally. Since online education is a complex process, the needs and expectations of instructors also show differences. However, the number of studies focused on English language instructors' job satisfaction is limited. Therefore, this study aims to find out online instructors' job satisfaction related to gender, years of teaching experience and the highest educational degree (bachelor, master's, and doctorate) variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The introduction of etutoring as a mechanism for student academic assistance and development in higher education is critical for skills to become relevant in labour markets. This line of reasoning supports (Ece & Kazazoğlu, 2021;Tuncay, 2021;Zalat, Hamed, & Bolbol, 2021)'s assertion that pupils would benefit from such an undertaking, particularly in light of the COVID-19 pandemic's negative impacts. True, because e-tutoring provides students with substantial fundamental benefits such as convenience, ease of participation, lower costs, and technology-driven benefits (Gherhes, Stoian & Farcasiu, 2021).…”
Section: Introductionsupporting
confidence: 63%
“…The introduction of etutoring as a mechanism for student academic assistance and development in higher education is critical for skills to become relevant in labour markets. This line of reasoning supports (Ece & Kazazoğlu, 2021;Tuncay, 2021;Zalat, Hamed, & Bolbol, 2021)'s assertion that pupils would benefit from such an undertaking, particularly in light of the COVID-19 pandemic's negative impacts. True, because e-tutoring provides students with substantial fundamental benefits such as convenience, ease of participation, lower costs, and technology-driven benefits (Gherhes, Stoian & Farcasiu, 2021).…”
Section: Introductionsupporting
confidence: 63%
“…This finding suggests that while instructors generally find online teaching to be satisfactory, there may still be room for improvement. Similarly, Ece and Kazazoğlu (2021) found that EFL instructors' job satisfaction level with teaching online was at moderate level. Understanding the specific aspects that contribute to this moderate level of satisfaction can help identify areas that may require attention and support.…”
Section: Resultsmentioning
confidence: 88%
“…Previous studies don't show consensus on the impact of years of experience on teachers' job satisfaction. While some found that that years of experience was not a predictor of overall teaching satisfaction (Camilli, 2004;Ece & Kazazoğlu, 2021;Topchyan & Woehler, 2021) others revealed that teaching experience is a determining factor for job satisfaction (Ferguson et al, 2012;Howe et al, 2018).…”
Section: Discussionmentioning
confidence: 99%